URGENSI NILAI PERUSAHAAN BANK UMUM DEVISA GO PUBLIC YANG TERDAFTAR DI BEI PADA MASA PANDEMI COVID 19 - Gustaf Naufan Febrianto (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to obtain information and results of banking business developments during the 2019-2020 period of the COVID-19 pandemic in Indonesia, seeing that the function of banking as an intermediary institution is seen from financial performance, namely capital, assets, management, earnings, and liquidity. Where capital is measured by (CAR), assets is measured by (NPL), management is measured by (ROE), earnings is measured by (BOPO), and liquidity is measured by (LDR) then the implications for the value of banking companies. The sample used in this study were 43 companies with 2 observations in 2019-2020. The data analysis of this research is the dependent sample t test (paired sample t-test) and then develops it with the financial ratio data owned so that it becomes a link between the variables in the study. The results showed: CAR between before and during the pandemic (Ho rejected, H1 accepted). The results of the H2 test show that there is a significant difference in bank performance, as measured by NPL between before and during the pandemic (Ho rejected, H2 accepted). The results of the H3 test show that there is an insignificant difference in bank performance, as measured by ROE between before and during the pandemic (Ho is accepted, H3 is rejected). The results of the H4 test show that there is a significant difference in bank performance, as measured by BOPO between before and during the pandemic (Ho is rejected, H4 is accepted), of course this fourth hypothesis is not accepted if it uses a high level of confidence. And the results of the H5 test show that there is an insignificant difference to bank performance, as measured by LDR between before and during the pandemic (Ho is accepted, H5 is rejected) and the implications for the value of banking companies are that performance affects the value of banking companies.